2016
DOI: 10.1161/jaha.116.004808
|View full text |Cite
|
Sign up to set email alerts
|

Association of Cholesterol Efflux Capacity With Clinical Features of Metabolic Syndrome: Relevance to Atherosclerosis

Abstract: BackgroundThe contribution of high‐density lipoprotein to cardiovascular benefit is closely linked to its role in the cellular cholesterol efflux process; however, various clinical and biochemical variables are known to modulate the overall cholesterol efflux process. The aim of this study was to evaluate the extent to which clinical and biological anomalies associated with the establishment of the metabolic syndrome modulate cholesterol efflux capacity and contribute to development of atherosclerosis.Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
1

Year Published

2018
2018
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(23 citation statements)
references
References 41 publications
2
20
1
Order By: Relevance
“…Therefore high‐glucose can have divergent effects on ABCA1‐expression dependent on the predominant transcription factor present within the cell. The ability of HDL to support cholesterol efflux is also modulated in individuals with the metabolic syndrome, particularly via SR‐BI and ABCG1 pathways, indicative that a multitude of steps in reverse cholesterol transport are reduced in the setting of cardiometabolic disease . Our study has shown that the microenvironment of obese adipose tissue results in increased ABCA1 activity, in contrast to peripheral cells from diabetic patients, again indicative that the primary source of tissue macrophages is a critical determinant of cellular ABCA1.…”
Section: Discussionmentioning
confidence: 60%
“…Therefore high‐glucose can have divergent effects on ABCA1‐expression dependent on the predominant transcription factor present within the cell. The ability of HDL to support cholesterol efflux is also modulated in individuals with the metabolic syndrome, particularly via SR‐BI and ABCG1 pathways, indicative that a multitude of steps in reverse cholesterol transport are reduced in the setting of cardiometabolic disease . Our study has shown that the microenvironment of obese adipose tissue results in increased ABCA1 activity, in contrast to peripheral cells from diabetic patients, again indicative that the primary source of tissue macrophages is a critical determinant of cellular ABCA1.…”
Section: Discussionmentioning
confidence: 60%
“…Cholesterol efflux capacity was progressively reduced in patients with MetS with increasing number of MetS risk factors [ 43 ]. It also was negatively correlated with fasting blood glucose and systolic blood pressure [ 43 ]. Efflux capacity is inversely associated with the risk of coronary heart disease (CHD) [ 44 ].…”
Section: Resultsmentioning
confidence: 99%
“…This is a retrospective, secondary analysis of a prospective cohort of consecutive patients between the ages of 18 and 75 years, seen in the Primary Cardiovascular Prevention Center at the Pitié‐Salpêtrière Hospital from January 2010 to June 2016. This cohort was initially designed to focus on cardiovascular risk evaluation and prevention and on atherosclerosis imaging . Therefore, included patients had to have at least one CVRF (e.g., age > 60 years in women and > 50 years in men; type 2 diabetes; dyslipidemia; high blood pressure; tobacco consumption) but no previous history of clinical cardiovascular events (e.g., myocardial infarction, coronary by‐pass surgery or coronary angioplasty, stroke).…”
Section: Methodsmentioning
confidence: 99%
“…This cohort was initially designed to focus on cardiovascular risk evaluation and prevention and on atherosclerosis imaging. (6,(13)(14)(15)(16) Therefore, included patients had to have at least one CVRF (e.g., age > 60 years in women and > 50 years in men; type 2 diabetes; dyslipidemia; high blood pressure; tobacco consumption) but no previous history of clinical cardiovascular events (e.g., myocardial infarction, coronary by-pass surgery or coronary angioplasty, stroke). For the purpose of this study we also excluded patients with excessive alcohol consumption (> 50 g/day in both men and women), any other identified cause of chronic liver disease including hepatitis B or C, and positive test for human immunodeficiency virus.…”
Section: Study Populationmentioning
confidence: 99%